iCook Herbs application: sharing platform for cuisine preparations - Rahim, Siti Nur Aliah; Moahmad Joha, Nurul Fatiha; Satingai, Nurul Izzatul (University Community Transformation Centre, Universiti Putra Malaysia, 2017)
Nowadays, most of the people do not know that the herbs can be used as ingredients in cuisine and hardly find the suitable recipe that consume specific herbs that they want. They may have an idea on how to make new cuisine but there is no platform to share their recipes. Therefore, there is a need of a medium to sharing new idea on recipes that consume herbs only. ICookHerbs is a web based application for the user to sharing their idea on new recipes consumes herbs as the ingredients. The system is consisting of recipes based on herbs and information of specific herbs in cuisine. The system is capable to provide a platform for user to share related idea of new variety of herbs recipe. The system is easy to use and also aids the user for searching the recipes that related with specific herb.